2015
DOI: 10.1590/2175-3539/2015/0192837
|View full text |Cite
|
Sign up to set email alerts
|

Bullying e Homofobia: Aproximações Teóricas e Empíricas

Abstract: ResumoEste estudo objetivou verificar como os fenômenos bullying e homofobia se aproximam, comparando a homofobia entre os atores do bullying (autor, alvo, alvo/autor e testemunhas) e observando se o conteúdo homofóbico é utilizado no bullying verbal. Foi realizado um estudo descritivo e quantitativo como método survey. Participaram 808 jovens com idade média de 14,9 anos (DP = 1,98), oriundos de 9escolas estaduais de Aracaju-SE, que responderam a um questionário contendo questões sociodemográficas sobre bully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
17

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
(16 reference statements)
1
3
0
17
Order By: Relevance
“…Furthermore, from this theoretical perspective, children's experiences and educational contexts are as relevant as the cognitive development (Smetana 2013), since experiences of close contact with members of different groups can affect the judgment, as demonstrated in the results. Many studies have shown that intergroup contact is associated with decreased prejudice (Hong and Garbarino 2012;Souza et al 2015); however, it is necessary to consider the proximity and quality of this contact, as brief contacts and/or superficial ones can contribute to the maintenance of stereotypes and foment prejudice (Heinze and Horn 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, from this theoretical perspective, children's experiences and educational contexts are as relevant as the cognitive development (Smetana 2013), since experiences of close contact with members of different groups can affect the judgment, as demonstrated in the results. Many studies have shown that intergroup contact is associated with decreased prejudice (Hong and Garbarino 2012;Souza et al 2015); however, it is necessary to consider the proximity and quality of this contact, as brief contacts and/or superficial ones can contribute to the maintenance of stereotypes and foment prejudice (Heinze and Horn 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we can cite the motivations for the exclusion. According to bullying studies, a frequent theme in the victimizations involves aspects of physical appearance (Souza et al 2015), which is still almost absent in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Quando agressores, utilizam da força para aterrorizar ou machucar o outro; enquanto vítimas, caracterizam-se como alvos do bullying; sendo vítimas-agressoras, são vítimas que também intimidam; e, finalmente, enquanto observadores, constituem-se como testemunhas que presenciam as situações de exposição das vítimas. Entretanto, independentemente do tipo de envolvimento das crianças e adolescentes no bullying, evidencia-se que estas são igualmente expostas a condições de vulnerabilidade, que afetam sua qualidade de vida e bem estar (Souza, Silva, & Faro, 2015).…”
Section: Introductionunclassified
“…Deste modo, sabemos que a dramática de vida da menina adolescente carrega sentidos diversos daqueles vividos por meninos adolescentes. A literatura científica sobre adolescência feminina abrange estudos sobre vários temas, tal como exemplificados a seguir: (i) sobre gravidez/maternidade na adolescência (Thomazini et al, 2016;Quaresma da Silva, 2016;Pacheco Sánchez, 2015); (ii) sobre transtornos alimentares (Peebles, 2017;Lindstedt, et al 2017;Martins e Petroski, 2015); (iii) sobre formas de violência e abuso (Brancaglioni e Fonseca, 2016; Souza et al, 2015) e (iv) sobre o empoderamento da mulher em condições sociais nas quais se destacam tanto dificuldades como possibilidades de mudança (Pisani, 2016), entre outros.…”
unclassified